The Criminal Prosecution of the International Trafficking of Human Beings in the Federal Justice System of Brazil - Dornelas, Luciano Ferreira (Oñati Socio-Legal Series, 2019)
The article analyzes the decisions of the organizations of the federal justice system in Brazil in charge of the cases concerning the international trafficking in persons. The research is an exploratory descriptive, quantitative and qualitative research of data. We analyze the inter-organizational relations and the basic assumptions of the decision making of the criminal justice system. The problem that we focus on answering is: how is the prosecution in criminal proceedings for international trafficking in persons implemented? The research is oriented by the organizational approach of the systemic theory and by the analysis of the network of governance for the fighting of trafficking in persons and it also involved the direct contact with the federal authorities that acted in the conduction of the investigations and criminal processes.